Development of an epub format e-book on dynamic electricity material - Moh. Rizal Fauzi Admojo; Atiqoh Atiqoh; Djoko Adi Walujo (Practice of The Science of Teaching Journal: Jurnal Praktisi Pendidikan, 2023)
The learning process for dynamic electricity is not yet optimal because electronic learning resources such as e-books have not been utilized properly. Dynamic electricity material must be taught using interesting and easy-to-use learning resources so students can study well at school or independently. This study aims to analyze the validity of the EPUB format e-book on dynamic electricity and student responses to the developed e-book. This type of research is the ADDIE model development research, which includes the stages of analysis, design, development, implementation, and evaluation. The data collected are validity, pretest, posttest, and student responses. Data analysis was carried out descriptively. This development research has produced an EPUB e-book on Physics in class X SMK/MAK. The media development model is very valid and used in SMK-level learning by going through several test stages on this development product. Based on the Material/Content Expert validation, the level of validity shows a final value of 82.44%. The media expert's assessment shows a percentage value of 89.60%, meaning the product is deemed fit. The results of student responses obtained an average of 86.77%, which can be concluded to be a very good response. The data acquisition results show that the epub format e-book media is very good for use in learning and means that the media can be used properly. Students respond to learning using e-books well, and it can be said that e-books in the EPUB format can be used properly by SMK students. Abstrak. Proses belajar pata materi listrik dinamis belum optimal, karena sumber belajar elektronik seperti e-book belum dimanfaatkan dengan baik. Materi listrik dinamis perlu diajarkan dengan sumber belajar yang menarik dan mudah digunakan agar peserta didik dapat belajar dengan baik di sekolah maupun secara mandiri. Penelitian ini bertujuan untuk menganalisis kevalidan e-book format EPUB materi listrik dinamis dan menganalisis respon siswa terhadap e-book yang dikembangkan. Jenis penelitian ini adalah penelitian pengembangan model ADDIE yang meliputi tahap analisis, desain, pengembangan, implementasi, dan evaluasi. Data yang dikumpulkan adalah kevalidan, pretest, posttest, dan respon peserta didik. Analisis data dilakukan secara deskriptif. Penelitian pengembangan ini telah menghasilkan sebuah e-book format EPUB pada mata pelajaran Fisika pada kelas X SMK/MAK. Dengan model pengembangan media sangat layak dan digunakan pada pembelajaran setingkat SMK dengan melalui beberapa tahapan uji pada produk pengembangan ini. Berdasarkan hasil validasi Ahli Materi/Isi bahwa tingkat kevalidan menunjukkan nilai akhir 82.44%. Pada penilaian dari Ahli Media menunjukkan nilai presentase sebesar 89.60%, artinya bahwa produk tersebut dinyatakan layak untuk digunakan. Hasil respon siswa memperoleh rata-rata sebesar 86.77% yang bisa disimpulkan memiliki respon yang sangat baik. Berdasarkan hasil perolehan data tersebut menunjukkan bahwa media e-book format epub sangat baik digunakan dalam pembelajaran dan diartikan bahwa media tersebut dapat digunakan semestinya. Siswa merespon pembelajaraan menggunakan e-book dengan baik dan bisa dikatakan e-book format EPUB dapat digunakan semestinya oleh siswa SMK.